GPU-accelerated interactive material aging - Günther, Tobias; Rohmer, Kai; Grosch, Thorsten (VMV 2012 - Vision, Modeling and Visualization, 2012)
A photorealistic appearance of a 3D scene is required in many applications today. Thereby, one vital aspect is the usage of realistic materials, for which a broad variety of reflectance models is available. When directly employing those models, surfaces always look new, which contrasts strongly the real objects surrounding us as they have undergone diverse kinds of aging processes. The literature already proposes a set of viable methods to simulate different aging phenomena, but all of them are computationally expensive and can thus only be computed off-line. Therefore, this paper presents the first interactive, GPU-accelerated method to simulate material aging in a given scene. Thereby, our approach allows artists to precisely control the course of the aging process. Our particle based method is capable to reproduce the most common deterioration phenomena in a few seconds, including plausible dirt bleeding, flow effects, corrosion and patina. © 2012 The Eurographics Association.
CRIS-Team Scopus Importer:2020-09-23